Trends in Digitalization and Cultural Identity: A Bibliometric Study on Local Traditions in the Digital Era - Loso Judijanto; Ni Putu Suda Nurjani; Ai Siti Nurmiati; Arief Fahmi Lubis (West Science Social and Humanities Studies, 2024)
This study explores the interplay between digitalization and cultural identity with a focus on local traditions in the digital era, using a bibliometric approach. By analyzing academic publications from key databases, the research identifies trends, thematic clusters, and emerging areas of interest in this interdisciplinary field. Results indicate that "digitalization" and "digital transformation" serve as central themes, connecting topics such as cultural heritage, social media, and industry 4.0. The study reveals an evolving research focus, transitioning from foundational efforts in cultural preservation to contemporary issues like digital leadership, innovation, and sustainability. Network analyses highlight significant global collaborations, with dominant contributions from countries like the United States, China, and the United Kingdom. However, disparities in representation suggest a need for more inclusive research that incorporates perspectives from underrepresented regions. Emerging technologies such as AI and VR offer promising directions for future exploration, while the tension between globalization and localization underscores the importance of balancing cultural authenticity with modern adaptations. This study provides a comprehensive overview of the research landscape and offers practical implications for policymakers, cultural practitioners, and technologists in fostering sustainable cultural preservation in the digital era.